On the Way to School, Tobago, B.W.I. - (:unkn) unknown (Waterman, the Hatter, Clothier and Outfitter,[Trinidad and Tobago];Printed in Germany, 2011)
This postcard shows a group of school children on the beach on their way to school.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Beaches--Trinidad and Tobago; School children--Trinidad and Tobago; Boys--Trinidad and Tobago; Girls--Trinidad and Tobago; Children--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hats--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Seashore--Trinidad and Tobago; Piers--Trinidad and Tobago; School--Trinidad and Tobago; [1930]